Cranium eroding sweat carcinoma - Arslan, Mehmet (Radiology and oncology (Ljubljana), 2005)
Background. Sweat gland carcinomas are rare turnors. Eccrine sweat gland carcinomas are also very rare, with only about 200 cases reported in the worldliterature and only one of them was eroding the cranium. Treatment modalities of these carcinomas are not well known. Case report. Our patient was 47 years old female. Since 1989, she was operated on six times because o fthe tumour relapses. After each operation, the pathological results were: sweat gland adenoma, sweat gland tumour, cylindroma, turban tumour, malign cylindiroma. That was her seventh relapse. On examination, a lesion of the size 10 x 6 cm was observed in the left parietal region. Computed tomography showed the lesion had the size of 11 x 5 cm, and was destroying the tabula externa, diploic region and tabula. The tumour was invading the dura and causing periost reaction. Surgery and postoperative radiotherapy treatment wasplanned because of malign transformation and risk of recurrence. Conclusians. Only one case with cranium erosion was reported in literature. Inour case, also intracranial extension of the tumor was observed.
Keywords: Diagnosis; glava; karcinom; Middle Age; Neoplasm Invasiveness; Novotvorba, invazivnost; Parietal Bone; Parietalna kost; Pathology; rak (medicina); Srednja leta; Surgery; Sweat Gland Neoplasms; znojne žleze; Znojnica, novotvorbe